A wideband spectropolarimetry study of the spatially resolved radio galaxies: Cygnus A & Hydra A - Sebokolodi, Makhuduga Lerato Lydia (Rhodes University, Faculty of Science, Department of Physics)
This study presented results from our deep, wideband, high-spectral and high-spatial-resolution polarisation observations of the two most powerful radio galaxies, namely Cygnus A and Hydra A, with the Jansky Very Large Array (JVLA). The high surface brightness and strong polarisation of these radio sources enabled detailed polarimetric imaging, providing images at 0.75"²"² resolution across 2âˆ’18 GHz and 2000 independent lines-of-sight across Cygnus A, and images at 1.5"²"² (2 âˆ’ 12 GHz) and 600 lines-of-sight across Hydra A. Our data revealed significant depolarisation and depolarisation structure, as well as deviations from a _2-law. We also found complicated structures in the Faraday spectra ranging from single-peaked to blended/resolved double- and multiple-peaked. The Faraday spectra of Hydra A were more multiple-peaked than Cygnus A. The fractional polarisation increased monotonically with increasing resolution, as expected. However, there were numerous lines-of-sight with complicated behaviour. We also found that the structure and complexity in the depolarisation increased at lower resolutions, suggesting substantial spatial structures across the lobes/tails. We fitted the 0.3"²"² (6âˆ’18 GHz) and 0.50"²"² (6âˆ’12 GHz) images of Cygnus A and Hydra A, respectively, with a simple model incorporating random, unresolved fluctuations in the cluster magnetic field to determine the high-resolution, high-frequency properties of the sources and the cluster. We found rotation measures (RM) between âˆ’5000 rad mâˆ’2 and +6400 rad mâˆ’2 across Cygnus A, and âˆ’2000 rad mâˆ’2 and +11900 rad mâˆ’2 across Hydra A, consistent with previous studies. From these derived properties, we generated predicted polarisation images of the sources at lower frequencies (< 6 GHz), convolved to 0.75"²"² for Cygnus A and 1.5"²"² for Hydra A. The predictions were remarkably consistent with the observed emission in both sources, providing strong support for the depolarisation being a result of unresolved fluctuations in the magnetic fields. We fitted various analytical models to the wideband data. We found that the data for both sources were inconsistent with a wholly mixed gas of thermal and synchrotron gas, particularly for regions withRM > 1000 rad mâˆ’2. Instead, the data required a dominant Faraday rotating screen in the foreground of the radio sources. The wideband modelling also showed preference towards models with at least two or more unresolved Faraday rotating patches. Single depolarising models fail to describe the data. This implies the presence of more than one depolarising screen in the vicinity of these sources. The observations were consistent with the lower-frequency depolarisation due to unresolved fluctuations on scales â‰³ 300âˆ’700 pc in the magnetic field or the electron density superposed on a partially ordered field component. Both the large-scale magnetic fields and unresolved magnetic field fluctuations are external to the radio emission. The magnetic fields around Cygnus A are located in the ambient cluster gas, the shocked gas in the boundary of the lobes or both, while the magnetic fields around Hydra A are most likely located in the ambient cluster gas.
Keywords: Radio astronomy; Radio galaxies; Faraday effect; Astrophysical spectropolarimetry; Intracluster medium; Cosmic magnetic fields